THE INFLUENCE OF EDUCATION LEVEL AND EMPLOYMENT SECTOR ON PER CAPITA CALORIE CONSUMPTION IN MAKASSAR CITY WITH INCOME AS AN INTERVENING VARIABLE” - Ramin, Ramin; Anshar, Muh. Ashary; Suwandaru, Rachman (Yayasan Education and Social Center, 2025)
This study aims to analyze the influence of education level and employment sector on per capita calorie consumption in Makassar City, with income as an intervening variable. Calorie consumption, as an indicator of the nutritional status of the population, is influenced by various factors, including education level and the type of employment sector, which ultimately determine household income. The research employs a quantitative approach using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The data were obtained from the March 2023 National Socio-Economic Survey (SUSENAS), involving 868 households and a total of 1,245 respondents in Makassar City. The findings reveal that (1).the education level has a negative and insignificant effect on income. (2).The employment sector has a positive and significant effect on income. (3).Income has a positive and significant effect on per capita calorie consumption. (4).Education level has a positive and significant effect on per capita calorie consumption. (5). The employment sector also has a positive and significant effect on per capita calorie consumption. (6) education level positively and significantly affects per capita calorie consumption through income. (7) the employment sector positively and significantly affects per capita calorie consumption through income. These findings are expected to provide valuable insights for local governments in formulating poverty alleviation and community welfare improvement policies.